Sharia Service Strategy Model Based on Islamic Business Ethics - Frastuti, Melia; Ritonga, Iskandar; Utami, Tri Niswati; Saputera, Satria; Veny, Harumi (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2025)
This study addresses the lack of an integrated model connecting Sharia compliance, Islamic business ethics, service quality, and social benefits in Islamic private hospitals. Using the Analytic Network Process (ANP) and expert judgments from hospital managers and regulators in Pekanbaru, the research develops a Sharia service strategy model grounded in Islamic business ethics.The findings show that Service Quality has the highest priority (0.261), followed by Maslahah (Social Benefits) (0.252), Sharia Compliance (0.246), and Islamic Business Ethics (0.241), indicating that all dimensions are equally important and mutually reinforcing. This study offers an original integrative framework that combines ethical, regulatory, operational, and social aspects, providing theoretical contributions to Islamic healthcare governance and practical guidance for strengthening Sharia-based hospital services.